Muscle-MRI and Functional Levels for the Evaluation of Upper Limbs in Duchenne Muscular Dystrophy: A Critical Review of the Literature - Lara Cristiano; Claudia Brogna; Giorgio Tasca; Tommaso Verdolotti; Marika Pane; Eugenio Mercuri (Medicina, 2022)
Many qualitative and quantitative Magnetic Resonance Imaging (MRI) techniques have been applied to evaluate muscle fat degeneration in Duchenne muscular dystrophy (DMD) subjects, but only few studies have focused on the upper limbs. We reviewed the literature in order to evaluate the association between muscle MRI findings and motor function levels in the upper limbs of DMD patients. Ten studies with upper limb muscle MRI data were available. Four explored all upper limb segments, while six explored only the forearm. Functional assessments were performed in nine of the ten studies. All of the studies showed a significant correlation between muscle MRI changes and motor function levels in both ambulant and non-ambulant DMD patients.